ChemInform Abstract: Rhodium‐Catalyzed C—H Alkylation of Indolines with Allylic Alcohols: Direct Access to β‐Aryl Carbonyl Compounds. Issue 12 (March 2016) - Han, Sang Hoon; Choi, Miji; Jeong, Taejoo; Sharma, Satyasheel; Mishra, Neeraj Kumar; Park, Jihye; Oh, Joa Sub; Kim, Woo Jung; Lee, Jong Suk; Kim, In Su
Abstract: The site‐selective C—H alkylation of various N‐heterocycles, such as indolines (I) and (IV) as well as pyrroles (VIII) with allylic alcohols is described.